The Economics of Cooking Energy Scenario in Arid Rajasthan - Ram, K Anantha; Bhati, G N; Goyal, Daulat (Annals of Arid Zone, 2016)
The analysis of non-commercial fuel supply and its use on randomly selected farms in arid Rajasthan revealed that about 60 per cent of fuel wood consumed on sample households was supplied by ones own farm. Fuelwood, dungcake and crop wastes accounted for 58,28 and 14 per cent of total noncommercial fuels used in cooking food. The per household annual consumption of non-commercial fuels ranged between 3. 13 to 5.62 t in different size of farms. However. the actual per capita energy derived from the non-commercial fuels consumed on sample farms was short by 22 per cent compared to requirement in country side conditions. It is inferred that the fuels are used inefficiently leading to diversion of valuable cowdung to hearths. The per farm cowdung used as fuel worth Rs. 108.00 was actually worth Rs. 302.00 in terms of nutrients (NPK) contained in it.